\(\dfrac{3}{8}\) - \(\dfrac{3}{4}\)+ \(\dfrac{1}{8}\)
Tính:
a) \(\dfrac{2}{3}+\dfrac{4}{3}\) \(\dfrac{9}{8}-\dfrac{1}{8}\) \(\dfrac{1}{6}+\dfrac{2}{3}\) \(\dfrac{3}{4}-\dfrac{7}{16}\)
b) \(9+\dfrac{2}{7}\) \(\dfrac{3}{8}+10\) \(7-\dfrac{2}{11}\) \(\dfrac{25}{4}-5\)
c) \(\dfrac{2}{3}\times\dfrac{1}{4}\) \(\dfrac{7}{11}\times\dfrac{11}{2}\) \(\dfrac{3}{7}:\dfrac{4}{9}\) \(\dfrac{9}{8}:\dfrac{3}{4}\)
d) \(8\times\dfrac{3}{7}\) \(\dfrac{3}{10}\times6\) \(6:\dfrac{5}{24}\) \(\dfrac{18}{7}:3\)
\(\dfrac{3}{2}X-0,2=\dfrac{3}{5}\)
\(\dfrac{1}{3}+x=\dfrac{3}{4}\)
\(1\dfrac{1}{2}x-\dfrac{2}{5}=\dfrac{1}{4}\)
\(\dfrac{11}{8}-\dfrac{3}{8}.x=\dfrac{1}{8}\)
giúp với
\(\dfrac{3}{2}x-0,2=\dfrac{3}{5}\)
\(\dfrac{3}{2}x-\dfrac{1}{5}=\dfrac{3}{5}\)
\(\dfrac{3}{2}x=\dfrac{3}{5}+\dfrac{1}{5}\)
\(\dfrac{3}{2}x=\dfrac{4}{5}\)
\(x=\dfrac{4}{5}:\dfrac{3}{2}\)
\(x=\dfrac{4}{5}\cdot\dfrac{2}{3}\)
\(x=\dfrac{8}{15}\)
\(\dfrac{1}{3}+x=\dfrac{3}{4}\)
\(x=\dfrac{3}{4}-\dfrac{1}{3}\)
\(x=\dfrac{9}{12}-\dfrac{4}{12}\)
\(x=\dfrac{5}{12}\)
\(1\dfrac{1}{2}x-\dfrac{2}{5}=\dfrac{1}{4}\)
\(\dfrac{3}{2}x-\dfrac{2}{5}=\dfrac{1}{4}\)
\(\dfrac{3}{2}x=\dfrac{1}{4}+\dfrac{2}{5}\)
\(\dfrac{3}{2}x=\dfrac{13}{20}\)
\(x=\dfrac{13}{20}:\dfrac{3}{2}\)
\(x=\dfrac{13}{20}\cdot\dfrac{2}{3}\)
\(x=\dfrac{13}{30}\)
\(\dfrac{11}{8}-\dfrac{3}{8}\cdot x=\dfrac{1}{8}\)
\(\dfrac{3}{8}\cdot x=\dfrac{11}{8}-\dfrac{1}{8}\)
\(\dfrac{3}{8}\cdot x=\dfrac{5}{4}\)
\(x=\dfrac{5}{4}:\dfrac{3}{8}\)
\(x=\dfrac{5}{4}\cdot\dfrac{8}{3}\)
\(x=\dfrac{10}{3}\)
\(\dfrac{2}{5}\) x \(\dfrac{3}{4}-\dfrac{1}{8}\) \(= \)
\(\dfrac{4}{3}+\dfrac{1}{3}-\dfrac{1}{5}=\)
\(\dfrac{9}{20}-\dfrac{3}{5}\) x \(\dfrac{1}{4}\)\(= \)
\(\dfrac{2}{8}+\dfrac{2}{3}:\dfrac{4}{5}\)\(=\)
\(\dfrac{2}{5}\times\dfrac{3}{4}-\dfrac{1}{8}=\dfrac{1}{5}\times\dfrac{3}{2}-\dfrac{1}{8}=\dfrac{3}{10}-\dfrac{1}{8}=\dfrac{24}{80}-\dfrac{10}{80}=\dfrac{14}{80}=\dfrac{7}{40}\\ \dfrac{4}{3}+\dfrac{1}{3}-\dfrac{1}{5}=\dfrac{5}{3}-\dfrac{1}{5}=\dfrac{25}{15}-\dfrac{3}{15}=\dfrac{22}{15}\\ \dfrac{9}{20}-\dfrac{3}{5}\times\dfrac{1}{4}=\dfrac{9}{20}-\dfrac{3}{20}=\dfrac{6}{20}=\dfrac{3}{10}\\ \dfrac{2}{8}+\dfrac{2}{3}:\dfrac{4}{5}=\dfrac{2}{8}+\dfrac{2}{3}\times\dfrac{5}{4}=\dfrac{2}{8}+\dfrac{1}{3}\times\dfrac{5}{2}=\dfrac{2}{8}+\dfrac{5}{6}=\dfrac{1}{4}+\dfrac{5}{6}=\dfrac{6}{24}+\dfrac{20}{24}=\dfrac{26}{24}=\dfrac{13}{12}\)
Tính:
\(\dfrac{1}{2}-\dfrac{3}{8}\) \(\dfrac{4}{3}-\dfrac{8}{15}\) \(\dfrac{5}{6}-\dfrac{7}{12}\)
\(\dfrac{11}{4}-\dfrac{9}{8}\) \(\dfrac{17}{16}-\dfrac{3}{4}\) \(\dfrac{31}{36}-\dfrac{5}{6}\)
\(\dfrac{1}{2}-\dfrac{3}{8}=\dfrac{4}{2\times4}-\dfrac{3}{8}=\dfrac{4}{8}-\dfrac{3}{8}=\dfrac{1}{8}\)
\(\dfrac{4}{3}-\dfrac{8}{15}=\dfrac{4\times5}{3\times5}-\dfrac{8}{15}=\dfrac{20}{15}-\dfrac{8}{15}=\dfrac{12}{15}=\dfrac{4}{5}\)
\(\dfrac{5}{6}-\dfrac{7}{12}=\dfrac{5\times2}{6\times2}-\dfrac{7}{12}=\dfrac{10}{12}-\dfrac{7}{12}=\dfrac{3}{12}=\dfrac{1}{4}\)
\(\dfrac{11}{4}-\dfrac{9}{8}=\dfrac{11\times2}{4\times2}-\dfrac{9}{8}=\dfrac{22}{8}-\dfrac{9}{8}=\dfrac{13}{8}\)
\(\dfrac{17}{16}-\dfrac{3}{4}=\dfrac{17}{16}-\dfrac{3\times4}{4\times4}=\dfrac{17}{16}-\dfrac{12}{16}=\dfrac{5}{16}\)
\(\dfrac{31}{36}-\dfrac{5}{6}=\dfrac{31}{36}-\dfrac{5\times6}{6\times6}=\dfrac{31}{36}-\dfrac{30}{36}=\dfrac{1}{36}\)
A,\(\dfrac{8}{9}:\dfrac{4}{5}+\dfrac{3}{5}\)
B,\(\dfrac{5}{8}\) + \(\dfrac{1}{4}\)
C,\(\dfrac{7}{8}\) x \(\dfrac{4}{7}\) +\(\dfrac{5}{9}\)
D,\(\dfrac{9}{8}:\dfrac{4}{3}-\dfrac{4}{7}\)
8/9 x 5/4 + 3/5 = 10/9 + 3/5 = 77/45
5/8 + 1/4 = 5/9 + 2/8 = 7/8
1/2 + 5/9 = 9/18 + 5/9 = 14/9
9/8 x 3/4 - 4/7 = 27/32 - 4/7 = 61/224
a) \(\dfrac{8}{9}:\dfrac{4}{5}+\dfrac{3}{5}=\dfrac{8}{9}\times\dfrac{5}{4}+\dfrac{2}{5}=\dfrac{10}{9}+\dfrac{2}{5}=\dfrac{50}{45}+\dfrac{18}{45}=\dfrac{68}{45}\)
b) \(\dfrac{5}{8}+\dfrac{1}{4}=\dfrac{5}{8}+\dfrac{2}{8}=\dfrac{6}{8}=\dfrac{3}{4}\)
c) \(\dfrac{7}{8}\times\dfrac{4}{7}+\dfrac{5}{9}=\dfrac{1}{2}+\dfrac{5}{9}=\dfrac{9}{18}+\dfrac{10}{18}=\dfrac{19}{18}\)
d) \(\dfrac{9}{8}:\dfrac{4}{3}-\dfrac{4}{7}=\dfrac{9}{8}\times\dfrac{3}{4}-\dfrac{4}{7}=\dfrac{27}{32}-\dfrac{4}{7}=\dfrac{61}{244}\)
A=8/9x5/4+3/5
=40/36+3/5
=10/9+3/5
=50/45+27/45=77/45
B=5/8+2/8=7/8
C=1/2+5/9
=9/18+10/18=19/18
Tính nhanh:
C=\(\dfrac{1}{8}\)x\(\dfrac{3}{2}\)-\(\dfrac{1}{8}\)x\(\dfrac{1}{4}\)+\(\dfrac{3}{8}\)x\(\dfrac{5}{4}\)
=1/8x(3/2-1/4)+3/8x5/4
=1/8x5/4+3/8x5/4
=5/4x(1/8+3/8)
=5/8
\(C=\dfrac{1}{8}\times\dfrac{3}{2}-\dfrac{1}{8}\times\dfrac{1}{4}+\dfrac{3}{8}\times\dfrac{5}{8}\)
\(C=\dfrac{1}{8}\times\left(\dfrac{3}{2}-\dfrac{1}{4}\right)+\dfrac{3}{8}\times\dfrac{5}{4}\)
\(C=\dfrac{1}{8}\times\dfrac{5}{4}+\dfrac{3}{8}\times\dfrac{5}{4}\)
\(C=\left(\dfrac{1}{8}+\dfrac{3}{8}\right)\times\dfrac{5}{4}\)
\(C=\dfrac{1}{2}\times\dfrac{5}{4}\)
\(C=\dfrac{5}{8}\)
a) Viết phân số đảo ngược của mỗi phân số sau: \(\dfrac{5}{8}\); \(\dfrac{3}{4}\); \(\dfrac{1}{2}\)
b) Tính
\(\dfrac{3}{7}:\dfrac{5}{8}\) \(\dfrac{8}{7}:\dfrac{3}{4}\) \(\dfrac{1}{3}:\dfrac{1}{2}\)
a) Các phân số đảo ngược là:
\(\dfrac{5}{8}\rightarrow\dfrac{8}{5};\dfrac{3}{4}\rightarrow\dfrac{4}{3};\dfrac{1}{2}\rightarrow\dfrac{2}{1}=2\)
b) \(\dfrac{3}{7}:\dfrac{5}{8}=\dfrac{3}{7}\times\dfrac{8}{5}=\dfrac{24}{35}\)
\(\dfrac{8}{7}:\dfrac{3}{4}=\dfrac{8}{7}\times\dfrac{4}{3}=\dfrac{32}{21}\)
\(\dfrac{1}{3}:\dfrac{1}{2}=\dfrac{1}{3}\times2=\dfrac{2\times1}{3}=\dfrac{2}{3}\)
\(\dfrac{-1}{8}+\dfrac{-5}{8}\)
\(\dfrac{-3}{7}+\dfrac{5}{7}\)
\(\dfrac{3}{5}+\dfrac{-7}{4}\)
\(\dfrac{-2}{3}+\dfrac{1}{5}\)
\(\dfrac{-2}{13}+\dfrac{-5}{26}\)
\(\dfrac{-4}{7}+\dfrac{1}{3}\)
-6/8=-3/2
2/7
Quy đồng được 12/20+-35/20=-23/20
Quy đồng được -10/15+3/15=-7/15
Quy đồng lên được -4/26+-5/26=-9/26
Quy đồng lên được: -12/21+7/21=-5/21 nhé
\(\dfrac{-1}{8}+\dfrac{-5}{8}=\dfrac{-6}{8}=\dfrac{-3}{4}\)
\(\dfrac{-3}{7}+\dfrac{5}{7}=\dfrac{2}{7}\)
\(\dfrac{3}{5}+\dfrac{-7}{4}=\dfrac{12}{20}+\dfrac{-35}{20}=\dfrac{-23}{20}\)
\(\dfrac{-2}{3}+\dfrac{1}{5}=\dfrac{-10}{15}+\dfrac{3}{15}=\dfrac{-13}{15}\)
\(\dfrac{2}{13}+\dfrac{-5}{26}=\dfrac{-4}{26}+\dfrac{-5}{26}=\dfrac{-9}{26}\)
\(\dfrac{-4}{7}+\dfrac{1}{3}=\dfrac{-12}{21}+\dfrac{7}{21}=\dfrac{-5}{21}\)
\(\dfrac{1}{3}+\dfrac{2}{3}=\)
\(\dfrac{4}{5}+\dfrac{5}{6}=\)
\(\dfrac{4}{5}-\dfrac{3}{5}=\)
\(\dfrac{9}{8}-\dfrac{4}{2}=\)
\(\dfrac{8}{5}x\dfrac{5}{8}=\)
\(\dfrac{6}{7}x\dfrac{4}{7}=\)
\(\dfrac{4}{5}:\dfrac{4}{5}=\)
\(\dfrac{5}{5}:\dfrac{5}{5}=\)
a,
\(\dfrac{1}{3}+\dfrac{2}{3}=\dfrac{3}{3}=1\)
\(\dfrac{4}{5}+\dfrac{5}{6}=\dfrac{24}{30}+\dfrac{25}{30}=\dfrac{49}{30}\)
\(\dfrac{4}{5}-\dfrac{3}{5}=\dfrac{1}{5}\)
\(\dfrac{8}{5}x\dfrac{5}{8}=\dfrac{1}{1}=1\)
\(\dfrac{6}{7}x\dfrac{4}{7}=\dfrac{24}{49}\)
\(\dfrac{4}{5}:\dfrac{4}{5}=\dfrac{4}{5}x\dfrac{5}{4}=\dfrac{1}{1}=1\)
\(\dfrac{5}{5}:\dfrac{5}{5}=\dfrac{5}{5}x\dfrac{5}{5}=\dfrac{1}{1}=1\)
1) \(\dfrac{1}{3}+\dfrac{2}{3}=\dfrac{1+2}{3}=\dfrac{3}{3}=1\)
2) \(\dfrac{4}{5}+\dfrac{5}{6}=\dfrac{24}{30}+\dfrac{25}{30}=\dfrac{24+25}{30}=\dfrac{49}{30}\)
3) \(\dfrac{4}{5}-\dfrac{3}{5}=\dfrac{4-3}{5}=\dfrac{1}{5}\)
4) \(\dfrac{9}{8}-\dfrac{4}{2}=\dfrac{9}{8}-2=\dfrac{9}{8}-\dfrac{16}{8}=-\dfrac{7}{8}\)
5) \(\dfrac{8}{5}\times\dfrac{5}{8}=\dfrac{8\times5}{5\times8}=\dfrac{40}{40}=1\)
6) \(\dfrac{6}{7}\times\dfrac{4}{7}=\dfrac{6\times4}{7}=\dfrac{24}{7}\)
7) \(\dfrac{4}{5}:\dfrac{4}{5}=\dfrac{4}{5}\times\dfrac{5}{4}=\dfrac{4\times5}{5\times4}=\dfrac{20}{20}=1\)
8) \(\dfrac{5}{5}:\dfrac{5}{5}=\dfrac{5}{5}\times\dfrac{5}{5}=\dfrac{5\times5}{5\times5}=\dfrac{25}{25}=1\)
Tính
a)5 \(\dfrac{3}{8}\)+ 1 \(\dfrac{1}{4}\)+ 3\(\dfrac{6}{7}\)
b) 2\(\dfrac{3}{8}\)- 1\(\dfrac{1}{4}\)+ 5 \(\dfrac{1}{3}\)